Akuntabilitas Perizinan Mendirikan Bangunan Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Perindustrian dan Tenaga Kerja Kota Bukittinggi - Fakhri Khalid; Simson Ginting; Sitti Hazzah Nur (SAJJANA: Public Administration Review, 2023)
The implementation of good governance lies in how far the collaboration between the three pillars of the state, namely the people, government and businessmen, is cohesive, harmonious and balanced. Together with the principle of prioritizing the public interest, the principles of social justice and equity will ensure that the implementation of development by all state apparatus runs using a good system of accountability. It is necessary to develop and implement an accountability system that is precise, clear, measurable and valid so that governance can run in an efficient and effective manner, clean and responsible and free from KKN. Keywords: public service, permit management